Which expression results from using the Distributive Property to rewrite −9.1(−4)−9.1(12)?

A. 9.1(−4+12)

B. −9.1(−4+12)

C. 9.1(−4−12)

D. −9.1(4−12)

Respuesta :

Answer:

B. −9.1(−4+12)

They distribute to make − 9.1 (− 4) − 9.1 (12)

Distribution is to multiply one value each from the value outside the parentheses (from the left side)

Ex. 1 (x + y) = 1(x) + 1(y) = 1x + 1y = x + y

Answer:

Choice B.  -9.1(-4+12)

Step-by-step explanation:

The distributive property in general is

a*(b+c) = a*b + a*c

In this case,

a = -9.1

b = -4

c = 12

So we have

a*(b+c) = a*b + a*c

-9.1*(-4+12) = -9.1(-4) + (-9.1)*(12)

-9.1(-4+12) = -9.1(-4) - 9.1(12)

------------

side note: the -9.1 shows up twice so that is factored out as its a common factor. The stuff left over (the -4 and the 12) is then added up.